The role of fullerenes in the environmental stability of polymer:fullerene solar cells. Issue 2 (17th January 2018) - Lee, Harrison Ka Hin; Telford, Andrew M.; Röhr, Jason A.; Wyatt, Mark F.; Rice, Beth; Wu, Jiaying; de Castro Maciel, Alexandre; Tuladhar, Sachetan M.; Speller, Emily; McGettrick, James; Searle, Justin R.; Pont, Sebastian; et al.
Abstract : Environmental stability is a common challenge for the commercialisation of low cost, encapsulation-free organic opto-electronic devices. Abstract : Environmental stability is a common challenge for the commercialisation of low cost, encapsulation-free organic opto-electronic devices. Understanding the role of materials degradation is the key to address this challenge, but most such studies have been limited to conjugated polymers. Here we quantitatively study the role of the common fullerene derivative PCBM in limiting the stability of benchmark organic solar cells, showing that a minor fraction (<1%) of photo-oxidised PCBM, induced by short exposure to either solar or ambient laboratory lighting conditions in air, consistent with typical processing and operating conditions, is sufficient to compromise device performance severely. We identify the effects of photo-oxidation of PCBM on its chemical structure, and connect this to specific changes in its electronic structure, which significantly alter the electron transport and recombination kinetics. The effect of photo-oxidation on device current–voltage characteristics, electron mobility and density of states could all be explained with the same model of photoinduced defects acting as trap states. Our results demonstrate that the photochemical instability of PCBM and chemically similar fullerenes remains a barrier for the commercialisation of organic opto-electronic devices.